Implementasi Maqashid Syariah dalam Pemberdayaan Ekonomi Masyarakat - Wulandari, Efriza Pahlevi; Saiban, Kasuwi; Munir, Misbahul (Invest Journal of Sharia & Economic Law, 2022)
Poverty is a social problem that must be immediately eradicated in people's lives. If there is no serious action to eliminate it, there will be many problems that arise due to poverty, such as crime, crime; even a strong person's faith can become weak when poverty strikes. one effort to reduce the level of poverty that exists, namely by empowering the community through the business sector (industry) to improve economic welfare. Islamic economic welfare is divided into 2, namely the welfare of the world and the hereafter. Welfare is material and spiritual welfare. Material welfare is obtained by increasing income to meet life's needs, while spiritual welfare draws closer to Allah SWT by maintaining maqashid sharia. The goal and hope of this Maqashid Syariah in improving the community's economy are to produce prosperity for the community itself, both in this world and in the hereafter